Immunometabolites Drive Bacterial Adaptation to the Airway - Tomlinson, Kira L.; Prince, Alice S.; Wong Fok Lung, Tania (Frontiers in Immunology, 2021)
Pseudomonas aeruginosa and Staphylococcus aureus are both opportunistic pathogens that are frequently associated with chronic lung infections. While bacterial virulence determinants are critical in initiating infection, the metabolic flexibility of these bacteria promotes their persistence in the airway. Upon infection, these pathogens induce host immunometabolic reprogramming, resulting in an airway milieu replete with immune-signaling metabolites. These metabolites are often toxic to the bacteria and create a steep selection pressure for the emergence of bacterial isolates adapted for long-term survival in the inflamed lung. In this review, we discuss the main differences in the host immunometabolic response to P. aeruginosa and S. aureus, as well as how these pathogens alter their own metabolism to adapt to airway metabolites and cause persistent lung infections.